Patient Identification Based on Patient Safety Objectives 1 Version Starkes 2024 in Hospitals : Identifikasi Pasien Berdasarkan Sasaran Keselamatan Pasien 1 Versi Starkes 2024 Di Rumah Sakit - Nugraheni, Sri Wahyuningsih; Prasetyo, Angga Bayu; Suprawita, Budi (Procedia of Engineering and Life Science, 2025)
Patient safety is a top priority in healthcare, and proper patient identification is the first step in preventing medical errors. A preliminary study at Indriati Hospital in Boyolali found misidentification and medication errors. This study aims to review the implementation of patient identification based on Patient Safety Goal (SKP) 1, STARKES 2024 version. This study used a descriptive qualitative method with a cross-sectional approach. Data collection techniques were carried out through in-depth interviews and observations of staff directly involved in the patient identification process. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results show that Indriati Hospital in Boyolali has regulations and SOPs for patient identification that meet standards. Patient identification is carried out using at least two identities such as full name and date of birth, and is supported by the use of identity bracelets. This process has been implemented before medical procedures and feeding. However, implementation in special situations such as disasters has not been optimal, and obstacles still exist in terms of interprofessional coordination. The conclusion of this study indicates that the implementation of patient identification has generally been running well, but there is still a need to improve staff understanding and collaboration between units. The suggestions given are to increase regular training, socialize SOPs, and strengthen cross-professional communication to ensure the accuracy of patient identification in various conditions